Manual dexterity: functional lateralisation patterns and motor efficiency - Serrien, Debroah J.; Sovijärvi-Spapé, Michiel M. (Elsevier, 2016)
Manual tasks are an important goal-directed ability. In this EEG work, we studied how handedness affects the hemispheric lateralisation patterns during performance of visually-driven movements with either hand. The neural correlates were assessed by means of EEG coherence whereas behavioural output was measured by motor error. The EEG data indicated that left- and right-handers showed distinct recruitment patterns. These involved local interactions between brain regions as well as more widespread associations between brain systems. Despite these differences, brain-behaviour correlations highlighted that motor efficiency depended on left-sided brain regions across groups. These results suggest that skilled hand motor control relies on different neural patterns as a function of handedness whereas behavioural efficiency is linked with the left hemisphere. In conclusion, the present findings add to our understanding about principles of lateralised organisation as a function of handedness.